Odpowiedzi

2010-04-11T18:57:30+02:00
A)6a +12b - 6a + 9b=21b
b)4b + 12 + 3a - 3b = 12 +1b + 3a
c) 7b + 7c - 3b - 6c = 4b + 1c
d)5a + 15 + 2b -3a -3b = 2a +15 -1b
e)18 + 6z - 8z -16 + 16 +2z = 18
f)-8x + 28 +12y +12y +12x = 4x + 28 + 24y
13 4 13
tak na marginesie pisze się -b anie -1b
2010-04-11T18:59:35+02:00
A) 6(a+2b) - 3(2a-3b)
6a + 12b - 6a + 9b
21b

b)4(b+3) + 3(a-b)
4b + 12 + 3a - 3b
b+12+3a

c) 7(b+c) -3(b+2c)
7b+7c-3b-6c
4b + c

d) 5 (a +3) +2b - 3 ( a+b )
5a+15+2b-3a-3b
2a+15-b

e) 6 (3+z)- 4 (2z +4) + 2 (8 +z)
18+6z -8z-16+16+2z
18

f) -4(2x - 7 - 3y ) - 12(-y- x)
-8x+28+12y+12y+12x
4x+28+24y
10 4 10
2010-04-11T19:06:09+02:00
A) 6a+12b-6a+9b
21b
b)4b+12+3a-3b
1b+12+3a
c)7b+7c-3b-6c
4b+c
d)5a+15+2b-3a-3b
2a+15-b
e)18+6z-8z-16+16+2z
18
f)-8x+14+12y+12y+12x
4x+28+14y
6 4 6